Asymmetric Information Transmission between a Transition Economy and the U.S. Market: Evidence from the Warsaw Stock Exchange - WU, Chunchi (Institutional Knowledge at Singapore Management University, 2003)
We investigate the international information transmission between the U.S. and Polish stock markets using daily return data from the S&P 500 Index and the Warszawski Indeks Gieldowy (WIG). The results show no volatility spillover between these two markets and that these two markets are not driven by a long-run common trend. However, there is a mean spillover running from the U.S. to the Warsaw Stock Exchange (WSE) in the EGARCH model. There is weak evidence of short-run influence of the U.S. market on the performance of the WSE. By contrast, the WSE has virtually no influence on the U.S. market